Blackthorne's Bride - Johnston, Joan 1948- (New York Dell Books, 2017)
"Two years have passed since Josie Wentworth was bought from the Sioux for a gold watch and whisked back to England by Marcus Wharton, the duke of Blackthorne. When Marcus breaks his promise to return Josie to America, she ends up as a maid in the home of his charming but neglected nephews. Once Josies long-lost family finds her, however, the suddenly wealthy heiress sets out to save the two boys from their indifferent uncle--and teach the duke a lesson in honor"--Amazon.com.
Keywords: Man-woman relationships -- Fiction; Heiresses -- Fiction; Nephews -- Fiction; Nobility -- Fiction; Revenge -- Fiction; England -- Social life and customs -- 19th century; Fiction; Romance fiction